KEUTAMAAN AYAH MENJADI WALI NIKAH DIBANDINGKAN ULAMA DALAM PERSPEKTIF HUKUM ISLAM - Hasmy, Misbahul Munir; Ridho, Muhammad; Harianto, Anggi (MAQASHIDUNA: JURNAL HUKUM KELUARGA ISLAM, 2025)
AbstractThe marriage contract is a very sacred moment, everyone definitely wants something perfect when the event is held, the choice of marriage guardian is sometimes a consideration in this case. Judging from classical jurisprudence books, the main person who acts as the marriage guardian is the woman's father, but in many places, when carrying out the marriage ceremony, the person who acts as the marriage guardian is a cleric or religious figure who is believed to bring blessings to the house. stairs later. The role of the marriage guardian is considered very important in marriage because if the guardian is not present then the marriage is not valid according to religion. In general, Islam has taught us all that the position of parents cannot be replaced by anyone else in terms of the priority of prayer and blessings for their children.Keywords: Father, Islamic Law, Marriage Guardian Abstrak:Akad nikah adalah sebuah momen yang sangat sakral, setiap orang yang pasti menginginkan sesuatu yang sempurna pada saat acara itu dilaksanakan, pemilihan wali nikah pun kadang menjadi pertimbangan dalam hal ini. Di tinjau dari kitab-kitab fiqih klasik yang paling utama menjadi wali nikah adalah bapak dari wanita tersebut, namun banyak juga di sebagian tempat ketika melaksanakan acara akad nikah ini, yang bertindak sebagai wali nikah adalah ulama atau tokoh agama yang dipercaya bisa mendatangkan keberkahan dalam rumah tangga nantinya. Peran wali nikah dianggap sangat penting dalam pernikahan karena jika wali tidak ada maka pernikahan tidak sah menurut agama. Secara garis besar Islam sudah mengajarkan kita semua bahwa kedudukan orang tua tidak bisa digantikan oleh orang lain dalam hal keutamaan doa dan keberkahan untuk anak-anaknya.Kata Kunci: Akad nikah, Wali nikah.